Numerical investigation of the mechanisms of ultrasound-modulated bioluminescence tomography - Zhang, Qimei; Mather, Melissa; Morgan, Stephen P. (Institute of Electrical and Electronics Engineers, 2015)
Objective: A hybrid imaging technique, Ultrasound Modulated Luminescence Tomography, that uses ultrasound to modulate diffusely propagating light has been shown to improve the spatial resolution of optical images. This paper is to investigate the underlying modulation mechanisms and the feasibility of applying this technique to improve the spatial resolution of bioluminescence tomography. Methods: Ultrasound Modulated Bioluminescence Tomography was studied numerically to identify the dominance of four factors (reduced optical scattering coefficient, optical absorption coefficient, refractive index, and luciferase concentration) on the depth of light modulation. In practice, an open source finite element method tool for simulation of diffusely propagating light, Near Infrared Fluorescence and Spectral Tomography, was modified to incorporate the effects of ultrasound modulation. The signal-to-noise ratios of detected modulated bioluminescent emissions are calculated using the optical and physical properties of a mouse model. Results: The modulation depth of the bioluminescent emission affected by the US induced variation of local concentration of the light emitting enzyme luciferase were at least two orders of magnitude greater than that caused by variations in the other factors. For surface radiances above approximately 107 photons/s/cm2/sr the corresponding SNRs are detectable with the current detector technologies. Conclusion: The dominant effect in generation of ultrasound modulated bioluminescence is ultrasound induced variation in luciferase concentration. The SNR analysis results confirm the feasibility of applying Ultrasound Modulated Bioluminescence Tomography in preclinical imaging of mice. Significance: The simulation model developed suggests ultrasound modulated bioluminescence tomography is a potential technique to improve the spatial resolution of bioluminescence tomography.